Effect of Organic Waste Addition into Animal Manure on Biogas Production Using Anaerobic Digestion Method - Arifan, Fahmi; Abdullah, Abdullah; Sumardiono, Siswo (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
One biomass form with a high potential to replace fossil fuels is biogas. Biogas yield production depends on the raw material or substrate used. This research was aimed to investigate a biogas production technique using an anaerobic digestion process based on a substrate mixture of a starter, cow dung, chicken manure, tofu liquid waste, and cabbage waste. The anaerobic digestion is a promised process to reduce waste while it is also producing renewable energy. Moreover, the process can digest high nutrients in the waste. The anaerobic digestion results showed that the combination producing the highest biogas amount was 200 mg starter mixed with a ratio of 70% cow dung, 15% chicken manure, and 15% tofu liquid waste. The larger the amount of cabbage waste, the lower the biogas production. The quadratic regression analysis was obtained for the variable with the highest yield and the estimated kinetic parameters based on the Gompertz equations revealed that the value of P∞ = 2,795.142 mL/gr.Ts, Rm = 113, 983.777 mL/gr.Ts, and t = 10.2 days. The results also concluded that the use of tofu liquid waste produced more biogas than cabbage waste. This study also successfully showed significant development in terms of the amount of biogas produced by adding organic waste to animal manure as the substrate used.